ASSESSING THE IMPACT OF THE DEMOGRAPHIC PROCESSES IN THE ARCTIC TERRITORIES ON THE SOCIAL DEVELOPMENT OF THE REGIONS PARTIALLY RELATED TO THE ARCTIC ZONE OF THE RUSSIAN FEDERATION - Shelomentsev, Andrey; Voronina, Lyudmila; Shikverdiev, Arif; Smirennikova, Elena; Ukhanova, Anna (Revista Inclusiones, 2020)
The study has been devoted to studying the impact of the demographic processes in the Arctic territories on the social development of the regions partially related to the Arctic zone of the country. The article offers the methodology for assessing the impact of demographic changes in the Arctic territories in 2018 as compared to 2012 on the social development of the regions partially related to the Arctic zone of the Russian Federation (the AZ RF). According to the results of the assessment, the impact matrix has been compiled. The result of the study can be used when developing and correcting program and strategic documents of all management levels aimed at regulating the demographic processes in the AZ RF.